Emotion Causes Targeted Forgetting of Established Memories - Strange, Bryan A.; Kroes, Marijn C.; Fan, Judith; Dolan, Raymond J. (Frontiers in Behavioral Neuroscience, 2010)
Reconsolidation postulates that reactivation of a memory trace renders it susceptible to disruption by treatments similar to those that impair initial memory consolidation. Despite evidence that implicit, or non-declarative, human memories can be disrupted at retrieval, a convincing demonstration of selective impairment in retrieval of target episodic memories following reactivation is lacking. In human subjects, we demonstrate that if reactivation of a verbal memory, through successful retrieval, is immediately followed by an emotionally aversive stimulus, a significant impairment is evident in its later recall. This effect is time-dependent and persists for at least six days. Thus, in line with a reconsolidation hypothesis, established human episodic memories can be selectively impaired following their retrieval.